Mutations in the tail and rod domains of the neurofilament heavy‐chain gene increase the risk of ALS - Marriott, Heather; Spargo, Thomas P.; Al Khleifat, Ahmad; Andersen, Peter M; Başak, Nazli A.; Cooper‐Knock, Johnathan; Corcia, Philippe; Couratier, Philippe; Carvalho, Mamede; Drory, Vivian; Gotkine, Marc; Landers, John E.; et al. (Annals of clinical and translational neurology, 2024)
Objective Neurofilament heavy‐chain gene (NEFH) variants are associated with multiple neurodegenerative diseases, however, their relationship with ALS has not been robustly explored. Still, NEFH is commonly included in genetic screening panels worldwide. We therefore aimed to determine if NEFH variants modify ALS risk. Methods Genetic data of 11,130 people with ALS and 7,416 controls from the literature and Project MinE were analysed. We performed meta‐analyses of published case–control studies reporting NEFH variants, and variant analysis of NEFH in Project MinE whole‐genome sequencing data. Results Fixed‐effects meta‐analysis found that rare (MAF <1%) missense variants in the tail domain of NEFH increase ALS risk (OR 4.55, 95% CI 2.13–9.71, p < 0.0001). In Project MinE, ultrarare NEFH variants increased ALS risk (OR 1.37 95% CI 1.14–1.63, p = 0.0007), with rod domain variants (mostly intronic) appearing to drive the association (OR 1.45 95% CI 1.18–1.77, pMadsen–Browning = 0.0007, pSKAT‐O = 0.003). While in the tail domain, ultrarare (MAF <0.1%) pathogenic missense variants were also associated with higher risk of ALS (OR 1.94, 95% CI 0.86–4.37, pMadsen–Browning = 0.039), supporting the meta‐analysis results. Finally, several tail in‐frame deletions were also found to affect disease risk, however, both protective and pathogenic deletions were found in this domain, highlighting an intricate architecture that requires further investigation. Interpretation We showed that NEFH tail missense and in‐frame deletion variants, and intronic rod variants are risk factors for ALS. However, they are not variants of large effect, and their functional impact needs to be clarified in further studies. Therefore, their inclusion in routine genetic screening panels should be reconsidered.